2008
DOI: 10.1074/jbc.m707697200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ceftriaxone Induction of Excitatory Amino Acid Transporter-2 Expression and Glutamate Uptake in Primary Human Astrocytes

Abstract: Glutamate is an essential neurotransmitter regulating brain functions. Excitatory amino acid transporter (EAAT)-2 is one of the major glutamate transporters primarily expressed in astroglial cells. Dysfunction of EAAT2 is implicated in acute and chronic neurological disorders, including stroke/ischemia, temporal lobe epilepsy, amyotrophic lateral sclerosis, Alzheimer disease, human immunodeficiency virus 1-associated dementia, and growth of malignant gliomas. Ceftriaxone, one of the ␤-lactam antibiotics, is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
247
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(256 citation statements)
references
References 50 publications
5
247
4
Order By: Relevance
“…Rothstein et al (2005) showed that CEF robustly stimulates GLT-1 expression, but not that of the other glutamate transporters, through increased GLT-1 gene transcription. This finding has been replicated in different laboratories (eg, Chu et al, 2007;Ouyang et al, 2007;Lee et al, 2008), including ours Omrani et al, 2009). We also showed that CEF increases GLT-1a expression in forebrain regions that regulate PPI of the startle .…”
Section: Discussionsupporting
confidence: 71%
“…Rothstein et al (2005) showed that CEF robustly stimulates GLT-1 expression, but not that of the other glutamate transporters, through increased GLT-1 gene transcription. This finding has been replicated in different laboratories (eg, Chu et al, 2007;Ouyang et al, 2007;Lee et al, 2008), including ours Omrani et al, 2009). We also showed that CEF increases GLT-1a expression in forebrain regions that regulate PPI of the startle .…”
Section: Discussionsupporting
confidence: 71%
“…However, because CFX induces the expression of the transcription factors NF-B and Nrf2, CFX may protect against cell death through multiple mechanisms. 66,67 In contrast to its administration before stroke, administration of CFX 30 minutes after the onset of ischemia did not significantly reduce stroke volume. 65 This lack of protection is not surprising, given that glutamate excitotoxicity is such an early event after onset of ischemia.…”
Section: Astrocytes Edema and Volume Regulation In Strokementioning
confidence: 88%
“…Ceftriaxone increases EAAT2 transcription in astrocytes through the nuclear factor-kB (NF-kB) signaling pathway by promoting nuclear translocation of p65 and activation of NF-kB (84). The mechanism of action of GPI-1046 is still not clear and must be investigated more in detail, although the initial indication suggests that immunophilins are involved in this upregulation (52).…”
Section: Foran and Trottimentioning
confidence: 99%